2021
DOI: 10.1038/s41598-021-00280-z
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation of antennal lobe composition among four hornet species

Abstract: Olfaction is a crucial sensory modality underlying foraging, social and mating behaviors in many insects. Since the olfactory system is at the interface between the animal and its environment, it receives strong evolutionary pressures that promote neuronal adaptations and phenotypic variations across species. Hornets are large eusocial predatory wasps with a highly developed olfactory system, critical for foraging and intra-specific communication. In their natural range, hornet species display contrasting ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…For the sake of consistency, we therefore refer to this group of glomeruli as T B in the remainder of this review, irrespective of the species being discussed. In both lineages, this cluster is located dorsally (according to neuroaxis; Strausfeld, 2002), close to the antennal nerve entrance (caudal), and is composed of a relatively high number of small and similar‐size glomeruli (Nakanishi et al ., 2010; Kelber et al ., 2010; Zube et al ., 2008; Couto et al ., 2017, 2021). This cluster also contrasts with other areas of the AL, as immunohistochemical studies revealed an identical lack of serotoninergic innervation in the T B cluster of carpenter ants and hornets (Fig.…”
Section: Specialised Sensory System For Chcs?mentioning
confidence: 99%
See 1 more Smart Citation
“…For the sake of consistency, we therefore refer to this group of glomeruli as T B in the remainder of this review, irrespective of the species being discussed. In both lineages, this cluster is located dorsally (according to neuroaxis; Strausfeld, 2002), close to the antennal nerve entrance (caudal), and is composed of a relatively high number of small and similar‐size glomeruli (Nakanishi et al ., 2010; Kelber et al ., 2010; Zube et al ., 2008; Couto et al ., 2017, 2021). This cluster also contrasts with other areas of the AL, as immunohistochemical studies revealed an identical lack of serotoninergic innervation in the T B cluster of carpenter ants and hornets (Fig.…”
Section: Specialised Sensory System For Chcs?mentioning
confidence: 99%
“…Consequently, nest‐mate recognition would become simpler in eusocial species, as individuals mostly interact with surrounding relatives. In our opinion, this hypothesis can be rejected in the case of the BaS subsystem, because the system is well developed in obligate eusocial species such as ants and hornets (Nakanishi et al ., 2010; McKenzie et al ., 2016; Couto et al ., 2021).…”
Section: Competing Evolutionary Hypotheses For the Origin Of A Specia...mentioning
confidence: 99%